Learning Motivation and Student Engagement as Predictors of Social Studies Understanding in Pre-Service Elementary Teachers - Sherly Ika Savitri; Sekar Purbarini Kawuryan; Anwar Senen; Fery Muhamad Firdaus; Aurelya Andini Putri (The Indonesian Institute of Science and Technology Research, 2026)
Students' understanding of elementary school social studies courses can be influenced by various internal and external factors, namely learning motivation and activity in the lecture process. This study aims to analyze the relationship between learning motivation and student activity with the understanding of basic elementary school social studies concepts in elementary school teacher education students. The approach in this study is a quantitative survey design with a cross-sectional design. There were 82 respondents, consisting of study groups E and F. The instruments used were questionnaires on learning motivation, activity, and understanding of elementary school social studies concepts. Data analysis was performed using descriptive statistics with JASP and Spearman's correlation test because the data were not normally distributed. The results of this study indicate a positive relationship between student activity and understanding of basic social studies concepts (p = 0.808; p < 0.001). Learning motivation has a significant positive relationship in the moderate category (p = 0.396; p < 0.001). In addition, there was a strong relationship between learning motivation and activity (p = 0.637; p < 0.001). These findings indicate that motivation and activity are important factors in building students' understanding of basic social studies concepts. The interrelationship between these two aspects is expected to support the effectiveness of the learning process in elementary school social studies basic concepts courses.